EVALUATION THE PHYSIOLOGICAL QUALITY OF Brachiaria brizantha cv. BRS 'Piata' SEEDS - Silva, Givanildo Zildo da [UNESP]; Martins, Cibele Chalita [UNESP]; Cruz, Jose de Oliveira [UNESP]; Jeromini, Tatiane Sanches [UNESP]; Alcantara Bruno, Riselane de Lucena (Univ Federal Uberlandia, 2017)
In a quality control program, seed vigor evaluation is of fundamental importance for the success of the program. The objective of this project was to evaluate the efficiency of several vigor tests to evaluate the physiological quality of Brachiaria brizantha cv. 'BRS Piata' seed lots and to preview seedling emergence in the field. Ten grass seed lots of the B. brizantha cv. 'BRS Piata' were evaluated by the following tests: germination, first count of germination, accelerated aging (43 degrees C/48 hours), cold test (seeds rolled in paper towel), seed water content before and after accelerated aging, electrical conductivity (50 and 75 mL, 25 degrees C and readings made 2, 4, 6, 8, and 24 hours after beginning the test), speed of germination index, and seedling emergence in sand substratum in the laboratory (26 +/- 3 degrees C) and daily seedling counts between the 7th and the 21th day after sowing. The treatment replications were distributed in the laboratory according to a completely random design with four replications. Seedling emergence in the field data were analyzed according to a randomized complete block design. Treatment means were compared by the Scott Knott test, at the 5% level of probability. The tests for germination and first germination count, seedling emergence and first emergence count in the sand, and accelerated aging are useful to assess the vigor of seed batches of the piata grass, and provide similar evidence to the seedling emergence in the field.
Keywords: Forage grasses; Pasture; Vigor tests; Seedling emergence in the field